Blood and Blood product Transfusion in sick Neonate: an Observational study at a Tertiary Care Hospital - Hassan , Mahmuda; Begum, Marium; Mannan, Abdul; Yasmeen, B H Nazma (Northern International Medical College Journal, 2025)
Background: Blood and blood product transfusions are common among hospitalized neonates in this advanced era at NICU, particularly in those of preterm low birth neonates. Objective: In this study we try to find out the types of transfusion in a neonatal intensive care unit among the sick neonates. Methods: Neonates who required blood or blood product transfusion between 1st Jan 2022 to 31st March 2023 at the neonatal intensive care Unit (NICU) of Ad- Women’s Medical college Hospital were included in this prospective observational study. Total 86 inborn and out-born babies with regular maternal antenatal care (ANC) check up with ANC book and other papers with good documentation were selected for the study. A structured questionnaire was used to obtain medical data i.e maternal and neonatal medical problems, indications for blood or other types of transfusion, type of blood products transfused and the frequency of transfusion during the hospital stay. We also observed maternal illnesses during pregnancy and neonatal demography as well as illnesses during the time of admission. Written consent was obtained from the parents or caregiver each time of blood and blood product transfusion as well as for the inclusion in the study. Statistical analysis was done with computer software SPSS version 16 (Statistical Package for Social Sciences). All data were processed and analyzed. Analyzed data were presented in the form of tables, charts, and graphs with due interpretation. Results: Out of 743 neonates who were admitted during the study period, 86 (10.9%) were studied who required one or more episode of blood or blood product transfusion. Five (5.80%) neonates required whole blood for the double volume exchange transfusion. Neonates required packed red blood cell (PRBC) for anemia was in 40(46.51%), fresh frozen plasma (FFP) for abnormal coagulation profile (with/ without active bleeding) in 64 (74.41 %), platelet for thrombocytopenia in 44(51.16%),albumin for hypoalbuminemia in 23(26.73%) and intravenous immunoglobulin (IVIG) in 9(11%) for severe thrombocytopenia. Four types of transfusion FFP+ PRBC +Albumin+ PLT required in 7(8.10%) neonates, 3 types of transfusion FFP+ platelet+ PRBC in 11(12.79%), FFP+ PLT+albumin in 3(3.48%) neonates, 2 types of transfusion FFP+PRBC in 9(10.46%), FFP+ albumin in 6(6.90%), FFP+ Platelet in 10(11.62%). Single type of transfusion in the form of Platelet or PRBC or FFP or whole blood in 7(8.12%), 10(11.62%), 11(12.79%) and 5(5.80%) respectively. So multiple transfusions were required in 53(61.62%) neonates. Conclusion: In this study we found that the Fresh frozen plasma transfusion was highest and the IVIG was the lowest number of transfusions in a neonatal intensive care unit. Northern International Medical College Journal Vol. 15 No. 1-2 July 2023-January 2024, Page 672-677